Assessment of New Expanded Porpholactones as Uv/Vis/Nir Chromophores for Dye-Sensitized Solar Cell Applications - Cardenas-Jiron, G; Pino-Rios, R; Montenegro-Pohlhammer, N (American Chemical Society, 2021)
Expanded porphyrins arise as an alternative for potential application as chromophores in dye-sensitized solar cells. (DSSCs). The modification of the core of these compounds provides remarkable changes in the photoelectronic behavior. In the present article, the improvement of its properties for a potential application as UV/vis/NIR chromophores in DSSCs has been studied, when an oxazolone moiety has replaced an imine ring in analogy to the porpholactones first synthesized by Crossley et al. (J. Chem. Soc., Chem. Commun. 1984, 920-922). These expanded porpholactones present a noticeable red shift as well as an increase in the intensity of the Q-bands regarding the parent compounds. The photophysical properties of Sapphyrin have been explored through DFT calculations and vibrationally resolved absorption spectra simulations. Energetic parameters showed favorable electron injection from the chromophore to the TiO2 semiconductor. In addition, aromaticity was analyzed and rationalized using magnetic and delocalization criteria. Results showed qualitatively similar trends between aromaticity descriptors and Q bands giving a great opportunity to the use this property in the rational design of chromophores. Finally, the nonequilibrium Green s function formalism shows the ability of expanded porpholactones in electron transport. © 2021 American Chemical Society.